Optical frequency domain imaging with a rapidly swept laser in the 1300nm bio-imaging window - Meleppat, Ratheesh Kumar (2018)
Optical frequency domain imaging system (OFDI) in the 1300nm biological imaging window is demonstrated by using a high speed frequency swept laser source. The output of the laser with central wave length of 1320nm is continuously tuned over a bandwidth of 100nm with a repetition rate of 16 KHz. The laser source has an instantaneous coherence length of 6mm and delivers an average power of 12mW. Axial resolution ~ 6μm in the biological tissue and peak sensitivity of 110dB are achieved. The experimentally determined values of the imaging parameters such as the axial resolution, sensitivity and depth range are found to be in good agreement with the theoretically estimated values. The developed system is capable of generating the images of size 512x1024 at a rate of 20 frames per second. High resolution and high contrast images of the finger nail and anterior chamber of a pig’s eye acquired using the developed OFDI system are presented, which demonstrate the feasibility of the system for in-vivo biomedical imaging applications.